2011
DOI: 10.1074/jbc.m110.196170
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Activity of α-Conotoxin PeIA at Nicotinic Acetylcholine Receptor Subtypes and GABAB Receptor-coupled N-type Calcium Channels

Abstract: ␣-Conotoxins are peptides from cone snails that target the nicotinic acetylcholine receptor (nAChR). RgIA and Vc1.1 have analgesic activity in animal pain models. Both peptides target the ␣9␣10 nAChR and inhibit N-type calcium channels via GABA B receptor activation, but the mechanism of action of analgesic activity is unknown. PeIA has previously been shown to inhibit the ␣9␣10 and ␣3␤2 nAChRs. In this study, we have determined the structure of PeIA and shown that it is also a potent inhibitor of N-type calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 33 publications
1
62
0
1
Order By: Relevance
“…Analgesic effects occurred at low doses (2 nmol or lower), with the 2-nmol dose producing effects greater than or equal to a dose of 500 nmol of the opioid analgesic morphine. Several studies have shown that some α-conotoxins block VGCCs via stimulation of GABA B receptors, suggesting that antinociceptive effects were mediated through blockade of N-type calcium channels (28)(29)(30)(31)(32)(33). However, some studies have not fully reproduced this effect (34,35), and we show that GeXIVA fails to block VGCCs.…”
Section: Discussionmentioning
confidence: 50%
“…Analgesic effects occurred at low doses (2 nmol or lower), with the 2-nmol dose producing effects greater than or equal to a dose of 500 nmol of the opioid analgesic morphine. Several studies have shown that some α-conotoxins block VGCCs via stimulation of GABA B receptors, suggesting that antinociceptive effects were mediated through blockade of N-type calcium channels (28)(29)(30)(31)(32)(33). However, some studies have not fully reproduced this effect (34,35), and we show that GeXIVA fails to block VGCCs.…”
Section: Discussionmentioning
confidence: 50%
“…1A). Despite their sequence differences, molecular modeling and solution NMR studies predict that PeIA, MII, and PnIA all share a similar three-dimensional backbone structure and occupy the acetylcholine binding pocket in approximately the same orientation (Rogers et al, 1999;Daly et al, 2011;Pucci et al, 2011). These differences and similarities suggest that specific residues of the peptides might be critical for binding to ␣6␤2-containing nAChRs.…”
Section: Discussionmentioning
confidence: 99%
“…PeIA[S9H,V10A,E14N] was generated using the NMR structural coordinates of PeIA (Daly et al, 2011) as a template and the mutagenesis function of PyMOL. MII was also generated from NMR structural coordinates (Hill et al, 1998), and PnIA was generated from X-ray crystallography coordinates (Hu et al, 1996).…”
mentioning
confidence: 99%
“…[6] Vc1.1 and RgIA are a9a10 nAChR subtype antagonists,and potently inhibit N-type (Ca v 2.2) and R-type (Ca v 2.3) calcium channels via GABA B receptor (GABA B R) activation. [8] Subsequently,t hree other conotoxins,P eIA, [9] AuIB [5d] and Vc1.2, [10] have also been shown to inhibit HVAc alcium channels via aGABA B R-dependent mechanism ( Figure 1A). [8] Subsequently,t hree other conotoxins,P eIA, [9] AuIB [5d] and Vc1.2, [10] have also been shown to inhibit HVAc alcium channels via aGABA B R-dependent mechanism ( Figure 1A).…”
mentioning
confidence: 99%